Allogeneic hematopoietic cell transplantation without fluconazole and fluoroquinolone prophylaxis - Heidenreich, Daniela; Kreil, Sebastian; Nolte, Florian; Reinwald, Mark; Hofmann, Wolf-Karsten; Klein, Stefan (Annals of hematology, 2016)
Fluoroquinolone (FQ) and fluconazole prophylaxis is recommended for patients undergoing allogeneic hematopoietic cell transplantation (alloHCT). However, due to an uncertain scientific basis and the increasing emergence of resistant germs, this policy should be questioned. Therefore, FQ and fluconazole prophylaxis was omitted in alloHCT at our center. In this retrospective analysis, all consecutive patients (n = 63) who underwent first alloHCT at our institution from September 2010 to September 2013 were included. Patients neither received FQ nor fluconazole prophylaxis. Day 100 mortality, incidence of febrile neutropenia, bacterial infections, and invasive fungal diseases (IFD) were assessed. Sixteen patients who started conditioning under antimicrobial treatment/prophylaxis due to pre-existing neutropenia (3/16), IFD (12/16), or aortic valve replacement (1/16) were excluded from the analysis. Finally, 47 patients were transplanted without prophylaxis as intended. Day 100 mortality was 9 %. Febrile neutropenia occurred in 62 % (29/47); 17/47 patients (36 %) experienced a blood stream infection (BSI) with detection of Gram-positive bacteria in 14 patients, Gram-negative bacteria in five patients, and candida in one patient, respectively. Coagulase-negative staphylococci were the most frequently isolated Gram-positive bacteria; 12/21 isolated Gram-positive and 3/6 Gram-negative bacteria were FQ resistant. In 21 % (10/47) of the patients, IFD (1x proven, 1x probable, and 8x possible) were diagnosed. To conclude, all three criteria, day 100 mortality, the incidence of IFD, and BSI, are in the range of published data for patients transplanted with FQ and fluconazole prophylaxis. These data demonstrate that alloHCT is feasible without FQ and fluconazole prophylaxis.